Propuesta de un plan de relaciones públicas para dar a conocer el proyecto y las ventajas de la construcción del nuevo aeropuerto y promover su aceptación a través de la comunicación externa frente a los futuros beneficiarios del nuevo Aeropuerto Internacional de Quito - Murgueitio Hidalgo, Rocío Estefanía (2012)
This Thesis project was made with the purpose of using Public relationships as a fundamental tool to make people aware of the project of the new Airport of Quito, also to stimulate its acceptation and make people aware of the advantages that come along with this great project. In the same way to find the appropriate strategies for the use of external communication that will be able to accomplish the project of the new airport of Quito. For this reason is that this Project was made on the basis of a previous research where it has shown the necessity of expressing a number of actions and strategies in order to improve the external communication, and is especially designed to take advantage of the making of a new airport pointing out all the advantages that it will bring. Proceeds as follows: in Chapter I perform a full investigation of air transport also talks about the current Mariscal Sucre Airport and the necessity of constructing a new airport outside the city. In Chapter II discusses about the totality communication, The Corporate Communication and Public Relationships as the principal key to the development of this project. According to the earlier sections in Chapter III talks about the current situation, all areas of economic, social, political and technological developments in relation to the New Quito Airport. Chapter IV uses the research tools needed to develop the project, made a graphical presentation of the results obtained through field research that was conducted with a previous study. Finally in Chapter V develops the proposed Public Relations plan for the New Quito Airport.